The peak oil debate - Laurel Graefe (Economic Review, 2009)
For the past half-century, a debate has raged over when peak oil will occurthe point at which output can no longer increase and production begins to level off or gradually decline. Determining how long the oil supply will last has become even more pressing because the world's energy supply still relies heavily on oil, and global energy demand is expected to rise steeply over the next twenty years. This article seeks to bring the peak oil debate into focus. The author notes that a number of factors cloud the energy outlook: Estimates of remaining resources are typically given as a range of probabilities and are thus open to interpretation. Variations also occur in estimates of future oil production and in the ways countries report their reserve data. The lack of a common definitional framework also confuses the debate. The author provides definitions of frequently used terms, delineating types of reserves and conventional versus nonconventional resources. She also discusses how technological innovations, government policies, and prices influence oil production. Regardless of the exact timing of peak oil production, the world must address the challenge of adapting to a new model of energy supply. Perhaps the world would be better served, the author notes, if the peak oil debate could be more solution-oriented, focusing on discovering the best way to transition to a world with less conventional oil rather than locking horns about discrepancies in terminology.
Keywords: Q40; Q41; 330; peak oil; oil supply; oil prices; conventional reserves; hotelling